2013
DOI: 10.1186/2008-2231-21-62
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of apo-9′-fucoxanthinone from the brown alga, Sargassum muticum

Abstract: BackgroundThe marine environment is a unique source of bioactive natural products, of which Sargassum muticum (Yendo) Fensholt is an important brown algae distributed in Jeju Island, Korea. S. muticum is a traditional Korean food stuff and has pharmacological functions including anti-inflammatory effects. However, the active ingredients from S. muticum have not been characterized.MethodsBioguided fractionation of the ethanolic extract of S. muticum, collected from Jeju island, led to the isolation of a norisop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
(26 reference statements)
2
31
0
Order By: Relevance
“…A latest report from S. muticum study showed that apo-9'-fucoxanthinone, belonging to the norisoprenoid family, effectively suppressed lipopolysaccharide (LPS)-induced nitric oxide and prostaglandin E2 production [18]. Our results also supported the anti-inflammatory effect of S. muticum.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A latest report from S. muticum study showed that apo-9'-fucoxanthinone, belonging to the norisoprenoid family, effectively suppressed lipopolysaccharide (LPS)-induced nitric oxide and prostaglandin E2 production [18]. Our results also supported the anti-inflammatory effect of S. muticum.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have investigated brown algae, such as Undaria pinnatifida (Wakame), Hijikia fusiformis (Hijiki), Laminaria japonica (Ma-Kombu), and Sargassum fulvellum [11,12]. However, the data on S. muticum, except in anti-inflammatory properties, [13,14] are to our knowledge not available. Until now, no studies have been performed in humans to determine the medicinal benefits of S. muticum including antioxidant, anti-inflammatory, hepatoprotective, antitumor, and cholesterol-lowering effects.…”
Section: Introductionmentioning
confidence: 93%
“…Sulfoglycerolipid demonstrated antibacterial [25] and antiviral activities [26]. The carotenoid fucoxanthin has an antioxidant and anticancer properties [27], and has shown anti-inflammatory effect [28]- [30]. Seasonal accumulation of these compounds may be of interest for applied purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are well-known for their antioxidant properties and protect HaCaT keratinocytes against UVBinduced phototoxic stress and DNA damage (Svobodová et al, 2009;Wu et al, 2009). Recently, it has been reported that apo-9 0 -fucoxanthinone isolated from S. muticum showed anti-inflammatory effects (Chae et al, 2013;Yang et al, 2013). Apo-9 0 -fucoxanthinone was a degradative product of fucoxanthin (Mori et al, 2004) and fucoxanthin is known for its antioxidant (Zheng et al, 2013), anti-inflammatory , anti-obesity (Maeda et al, 2005), antitumor , and UVB-preventative activities (Urikura et al, 2011).…”
Section: Discussionmentioning
confidence: 99%